2009
DOI: 10.1111/j.1349-7006.2009.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical studies of anticancer agent‐incorporating polymer micelles

Abstract: The size of anticancer agent-incorporating micelles can be controlled within the diameter range of 20-100 nm to ensure that they do not penetrate normal vessel walls. With this development, it is expected that the incidence of drug-induced side-effects may be decreased owing to the reduced drug distribution in normal tissue. Micelle systems can also evade non-specific capture by the reticuloendothelial system because the outer shell of a micelle is covered with polyethylene glycol. Consequently, a polymer mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
308
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(311 citation statements)
references
References 43 publications
3
308
0
Order By: Relevance
“…Polymer Therapeutics includes five different groups: polymeric drugs, polymers with inherent activity [5,6] polymer-protein conjugates [3,7,8]; polyplexes which are multi-component systems developed as non-viral vectors for gene/small interfering ribonucleic acid (siRNA) delivery [9,10], polymeric micelles where the bioactive agent is covalently bound [11,12] and polymer-drug conjugates [3] ( Figure 1). This field has been exhaustively revised and the following background references are recommended [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer Therapeutics includes five different groups: polymeric drugs, polymers with inherent activity [5,6] polymer-protein conjugates [3,7,8]; polyplexes which are multi-component systems developed as non-viral vectors for gene/small interfering ribonucleic acid (siRNA) delivery [9,10], polymeric micelles where the bioactive agent is covalently bound [11,12] and polymer-drug conjugates [3] ( Figure 1). This field has been exhaustively revised and the following background references are recommended [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that intratumoral pH value in solid tumors was around 6.5. 50 Therefore, in the in vitro transfection test, the pH value of cell culture medium without serum was adjusted to 6.5 to mimic the acidic microenvironment of tumor cells. It was found that CMCS-CLDPD achieved similar transfection efficiency to CLDPD at pH 6.5 but with lower transfection efficiency at pH 7.4 ( Figure 13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the polymeric micelles are considered as promising carriers of water-insoluble anticancer drugs. Currently, several promising candidates are in clinical trials (Lee et al, 2008;Matsumura & Kataoka, 2009). …”
Section: Introductionmentioning
confidence: 99%